ERO1L Is a Novel and Potential Biomarker in Lung Adenocarcinoma and Shapes the Immune-Suppressive Tumor Microenvironment - Liu, Lihui; Wang, Chao; Li, Sini; Qu, Yan; Xue, Pei; Ma, Zixiao; Zhang, Xue; Bai, Hua; Wang, Jie (Frontiers in Immunology, 2021)
Background The endoplasmic reticulum oxidoreductin-1-like (ERO1L) gene encodes an endoplasmic reticulum luminal localized glycoprotein known to associated with hypoxia, however, the role of ERO1L in shaping the tumor immune microenvironment (TIME) is yet to be elucidated in lung adenocarcinoma (LUAD). Methods In this study, raw datasets (including RNA-seq, methylation, sgRNA-seq, phenotype, and survival data) were obtained from public databases. This data was analyzed and used to explore the biological landscape of ERO1L in immune infiltration. Expression data was used to characterize samples. Using gene signatures and cell quantification, stromal and immune infiltration was determined. These findings were used to predict sensitivity to immunotherapy. Results This study found that ERO1L was significantly overexpressed in LUAD in comparison to normal tissue. This overexpression was found to be a result of hypomethylation of the ERO1L promoter. Overexpression of ERO1L resulted in an immune-suppressive TIME via the recruitment of immune-suppressive cells including regulatory T cells (Tregs), cancer associated fibroblasts, M2-type macrophages, and myeloid-derived suppressor cells. Using the Tumor Immune Dysfunction and Exclusion (TIDE) framework, it was identified that patients in the ERO1Lhigh group possessed a significantly lower response rate to immunotherapy in comparison to the ERO1Llow group. Mechanistic analysis revealed that overexpression of ERO1L was associated with the upregulation of JAK-STAT and NF-κB signaling pathways, thus affecting chemokine and cytokine patterns in the TIME. Conclusions This study found that overexpression of ERO1L was associated with poor prognoses in patients with LUAD. Overexpression of ERO1L was indicative of a hypoxia-induced immune-suppressive TIME, which was shown to confer resistance to immunotherapy in patients with LUAD. Further studies are required to assess the potential role of ERO1L as a biomarker for immunotherapy efficacy in LUAD.